Gemcitabine plus erlotinib followed by capecitabine versus capecitabine plus erlotinib followed by gemcitabine in advanced pancreatic cancer: final results of a randomised phase 3 trial of the ‘Arbeitsgemeinschaft Internistische Onkologie’ (AIO-PK0104) - Heinemann, Volker; Vehling-Kaiser, Ursula; Waldschmidt, Dirk; Kettner, Erika; Märten, Angela; Winkelmann, Cornelia; Klein, Stefan; Kojouharoff, Georgi; Gauler, Thomas C; von Weikersthal, Ludwig Fischer; Clemens, Michael R; Geissler, Michael; et al. (Gut, 2013)
Objective AIO-PK0104 investigated two treatment strategies in advanced pancreatic cancer (PC): a reference sequence of gemcitabine/erlotinib followed by 2nd-line capecitabine was compared with a reverse experimental sequence of capecitabine/erlotinib followed by gemcitabine. Methods 281 patients with PC were randomly assigned to 1st-line treatment with either gemcitabine plus erlotinib or capecitabine plus erlotinib. In case of treatment failure (eg, disease progression or toxicity), patients were allocated to 2nd-line treatment with the comparator cytostatic drug without erlotinib. The primary study endpoint was time to treatment failure (TTF) after 1st- and 2nd-line therapy (TTF2; non-inferiority design). KRAS exon 2 mutations were analysed in archival tumour tissue from 173 of the randomised patients. Results Of the 274 eligible patients, 43 had locally advanced and 231 had metastatic disease; 140 (51%) received 2nd-line chemotherapy. Median TTF2 was estimated with 4.2 months in both arms; median overall survival was 6.2 months with gemcitabine/erlotinib followed by capecitabine and 6.9 months with capecitabine/erlotinib followed by gemcitabine, respectively (HR 1.02, p=0.90). TTF for 1st-line therapy (TTF1) was significantly prolonged with gemcitabine/erlotinib compared to capecitabine/erlotinib (3.2 vs 2.2 months; HR 0.69, p=0.0034). Skin rash was associated with both TTF2 (rash grade 0/1/2–4:2.9/4.3/6.7 months, p<0.0001) and survival (3.4/7.0/9.6 months, p<0.0001). Each arm showed a safe and manageable toxicity profile during 1st- and 2nd-line therapy. A KRAS wild-type status (52/173 patients, 30%) was associated with an improved overall survival (HR 1.68, p=0.005). Conclusion Both treatment strategies are feasible and demonstrated comparable efficacy; KRAS may serve as biomarker in patients with advanced PC treated with erlotinib. Trial registration number This study was registered at ClinicalTrials.gov, number NCT00440167. Significance of this study What is already known on this subject? Gemcitabine-based chemotherapy remains an international standard of care for patients with non-resectable, advanced pancreatic cancer (PC). Anti-EGFR treatment with the tyrosine kinase inhibitor erlotinib, as well as chemotherapy intensification by application of the FOLFIRINOX regimen, both significantly improved overall survival in randomised phase 3 trials. The optimal (sequential) regimen for the use of gemcitabine, erlotinib and the oral fluoropyrimidine capecitabine remains unclear in advanced PC. Molecular predictors for the efficacy of anti-EGFR treatments in PC have not been defined up to now. What are the new findings? The sequential use of gemcitabine, erlotinib and capecitabine is safe and equally effective in PC; gemcitabine appears to be more effective in 1st- and 2nd-line therapy than capecitabine and therefore remains the preferred combination partner for erlotinib. Skin rash is strongly correlated with efficacy outcome measures in PC patients treated with erlotinib. KRAS wild-type status appears to be associated with improved overall survival in patients treated with erlotinib in this AIO study. Significance of this study How might it impact on clinical practice in the foreseeable future? The benefit of adding erlotinib to chemotherapy is restricted to patients that experience skin rash during treatment; non-rash patients are characterised by a very poor outcome and need to be offered novel treatment strategies. Second-line salvage chemotherapy is effective and safe in selected PC patients. KRAS could serve as the first biomarker for improved survival in erlotinib-treated patients; the predictive value of KRAS for erlotinib efficacy remains to be defined prospectively.